Clinico-Epidemiological Characteristics of Elderly Patients Presented in a Newly Established Geriatric Wing of a Tertiary Level Hospital in Bangladesh (Journal of Chittagong Medical College Teachers' Association, 2023)
Background: Ageing is an emerging issue for global public health including Bangladesh which is underwent a demographic transition and experiencing an increasing proportion of the elderly population. We conducted this study to document the characteristics of the patients admitted into a newly established geriatric centre in a tertiary-level hospital in Bangladesh.Materials and methods: We conducted this descriptive cross-sectional study among 194 older adults admitted into the geriatric centre of Chittagong Medical College Hospital of Bangladesh. A structured questionnaire was utilized to collect the information. The study participants’ Socio-Economic (SE) class was determined by modified Kuppuswamy’s classification. The data were analyzed with Stata SE 17.0 for descriptive and inferential statistics.Results: Among the 194 participants, 66.5% represented the middle SE class while about one-fourth were from the Upper SE class. Gender (p-value: 0.029) education (pvalue: